2020
DOI: 10.1101/2020.12.23.423848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Correlations and Confounding Variables for Quantification of Retinal Ganglion Cells Based on Optical Coherence Tomography using Diversity Outbred Mice

Abstract: PurposeDespite popularity of optical coherence tomography (OCT) in glaucoma studies, it’s unclear how well OCT-derived metrics compare to traditional measures of retinal ganglion cell (RGC) abundance. Here, Diversity Outbred (J:DO) mice are used to directly compare ganglion cell complex (GCC)-thickness measured by OCT to metrics of retinal anatomy measured ex vivo with retinal wholemounts or optic nerve cross sections.MethodsJ:DO mice (n = 48) underwent OCT and fundoscopic exams, with GCC-thickness measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…A recent meta-analysis on this topic also showed a stronger association with GC-IPL thickness compared to mRNFL thickness between DM patients with no DR and controls [ 25 ]. Our findings, together with prior work from others, suggest that GC-IPL thickness may be a good marker for evaluation of DRN and animal studies suggest that thinning of GC-IPL may represent loss of ganglion cells [ 26 ]. Direct visualization of ganglion cells in-vivo would help further elucidate this.…”
Section: Discussionsupporting
confidence: 73%
“…A recent meta-analysis on this topic also showed a stronger association with GC-IPL thickness compared to mRNFL thickness between DM patients with no DR and controls [ 25 ]. Our findings, together with prior work from others, suggest that GC-IPL thickness may be a good marker for evaluation of DRN and animal studies suggest that thinning of GC-IPL may represent loss of ganglion cells [ 26 ]. Direct visualization of ganglion cells in-vivo would help further elucidate this.…”
Section: Discussionsupporting
confidence: 73%
“…While there is a possibility this analysis could introduce variation, previous publications have shown that retinal parameters have high intraocular correlation in J:DO mice. 19 Furthermore, we have shown that BRN3A antibody staining is not significantly different between eyes in C57BL/6J mice. However, we cannot discount the possibility that enucleation of one eye may result in optic nerve and/or RGC damage in the fellow eye, 50 which would have the potential to influence the results presented here.…”
Section: Discussionmentioning
confidence: 71%
“…J:DO mice lack known overt retinal degenerative mutations, such as rd1 or rd8, 17,18 and have normal appearing retinas. 19 J:DO have approximately 45 million segregating genetic variations and encompass the majority of all existing genetic diversity in laboratory strains of mice. J:DO mice have had multiple generations of opportunity for meiotic recombination, which makes them useful for analysis of complex traits, [20][21][22][23][24] such as the response to blast.…”
mentioning
confidence: 99%
“…Lyst ) with healthy optic nerves ( n =5 nerves); C57BL/6J that had been subjected to either blast-induced traumatic brain injury (TBI blast) within an enclosed chamber or sham treatment (TBI sham; n= 27 nerves); 3, 4, 22 and Diversity Outbred (J:DO) with healthy optic nerves but predicted to exhibit genetic background-dependent natural variability in optic nerve features ( n= 13 nerves). 38, 39 Tissues in the current study were collected from mice contributing to prior publications, 40, 41 however all data reported herein arise from new analyses performed uniquely for this study. All mice used in this study were originally purchased from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%